2020
DOI: 10.1002/cam4.3353
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a lipid metabolism‐related and immune‐associated prognostic signature for hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…Univariate and multivariate Cox analyses confirmed the independent prognostic value of the risk signature. Several studies in recent years have identified metabolism-related risk signatures for effectively predicting OS and have uncovered the importance of metabolism-related genes in the process of HCC development ( Hu et al, 2020 ; Wu et al, 2021 ). Zhu’s study built a lipid metabolism-related prognostic signature and revealed that lipid metabolism-related genes are closely correlated with clinical characteristics, immune cells, and multiple biological functions of HCC ( Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Univariate and multivariate Cox analyses confirmed the independent prognostic value of the risk signature. Several studies in recent years have identified metabolism-related risk signatures for effectively predicting OS and have uncovered the importance of metabolism-related genes in the process of HCC development ( Hu et al, 2020 ; Wu et al, 2021 ). Zhu’s study built a lipid metabolism-related prognostic signature and revealed that lipid metabolism-related genes are closely correlated with clinical characteristics, immune cells, and multiple biological functions of HCC ( Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hilvo et al (2011) demonstrated that the lipids in the breast cancer tissue were correlated with tumor progression and patient survival. Moreover, previous studies have demonstrated that lipid metabolism related genes (LMRGs) had potent prognostic potential in multiple types of tumors, including ovarian carcinomas (Zheng et al, 2020), lung adenocarcinoma (LAUD) (Li et al, 2020), pancreatic cancer (Ye et al, 2021), hepatocellular carcinoma (HCC) (Hu et al, 2020), renal cell carcinoma (RCC) (Bao et al, 2019) and diffuse gliomas (Wu et al, 2019). As such, targeting lipid metabolism has been regarded as a novel therapeutic strategy for tumor treatment (Visweswaran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lipids have been gradually included in the emerging prognostic indices, such as Prognostic Nutritional Index (PNI) [ 35 ], Controlling Nutritional Status (CONUT) score [ 36 ] and Naples prognostic score (NPS) [ 37 ]. In addition, lipid metabolism-related signature also showed prognostic significance for some cancers [ 38 ]. The hypothesis that tumors are driven by dysregulated metabolism largely explained the significance of metabolomics in tumor prognosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%